Contributions of Agroforestry Practice Towards Reducing Poverty at Keshabpur Upazila of Jessore District A Case Study (Journal of Environmental Science and Natural Resources, 2013)
The systematic agroforestry practice is being popular day by day in Jessore district of Bangladesh. Considering the situation, the present study aims to know the farmers attitude and perception about agroforestry practice and to find out the potentialities of agroforestry to reduce poverty at the study area viz., Keshabpur upazila of Jessore district. Mixed method by using semi-structured questionnaires was followed in the field survey. The results illustrated that the respondents preferred agricultural practice (average 58.45% of their total lands) as their major land use followed by homestead and agroforestry land uses (31.75%). Agroforestry was getting popularity as well as socially and ecologically acceptable at this area due to the diversified outcomes of this practice. The small land holders (possession >1 acre) were the most interested among the respondents to practice agroforestry. The less poor agroforestry farmers change of income was also higher than the poor farmers. The increased production and income facilitated the villagers to reduce their poverty to some extent and thus they had better access to their daily necessities which helped them to attain a minimal standard of living.DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14829 J. Environ. Sci. & Natural Resources, 5(2): 267-274 2012